2008
DOI: 10.1002/ibd.20367
|View full text |Cite
|
Sign up to set email alerts
|

The INSPIRE study: Are different personality traits related to disease-specific quality of life (IBDQ) in distressed patients with ulcerative colitis and Crohnʼs disease?

Abstract: Although the emotional function subscale was related to neuroticism in both UC and CD, the social function subscale and total IBDQ were related to different personality traits in UC and CD. Personality traits should be taken into account when using IBDQ in studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 56 publications
(52 reference statements)
5
30
1
1
Order By: Relevance
“…The MHLC has previously been used in IBD patients 62 and other chronic disease groups and is therefore likely to be valid. Thus, the lack of association between psychological determinants of health beliefs and probiotic use indicates the appeal of probiotics to individuals across the range of health locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…The MHLC has previously been used in IBD patients 62 and other chronic disease groups and is therefore likely to be valid. Thus, the lack of association between psychological determinants of health beliefs and probiotic use indicates the appeal of probiotics to individuals across the range of health locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] A few studies have reported differences in personality traits according to IBD type, with CD patients being significantly more extroverted and having higher psychoticism personality scores than UC patients, but neuroticism scores were similar. 62,65 Personality traits have not been addressed in the pediatric HRQOL literature.…”
Section: Personality Traitsmentioning
confidence: 93%
“…15 These normative data can then be used to compare the burden of illness of a specific condition to that of other chronic illnesses, and also healthy populations. 16 Generic measures have been utilized in HRQOL studies in both adults 17,18 and children with IBD. 19,20 Disease-specific instruments are also multidimensional problem lists, but focus on concerns relevant to a particular illness.…”
Section: Hrqol Instrumentsmentioning
confidence: 99%
“…Important personality factors in ulcerative colitis were neuroticism and locus of control, while in Crohn's disease there was social conformity/desirability together with neuroticism 46 . IBDs often have high level of dependence on others and low levels of hostility and aggression 47 .…”
Section: Ibd Related Psychological and Psychiatric Problemsmentioning
confidence: 99%